GGCT participates in the malignant process of hepatocellular cancer cells by regulating the PTEN/PI3K/AKT pathway through binding to EZH2 - He, Junbo; Wang, Liangzhi; Lv, Mengjia; Yuan, Yiming (Discover. Oncology, 2025)
Background γ-Glutamylcyclotransferase (GGCT) is implicated in multiple types of cancer diseases. Nevertheless, the roles and relevant mechanisms of GGCT in hepatocellular carcinoma (HCC) remain vague. Methods GGCT expression in HCC and its effect on patient survival curve in HCC were evaluated utilizing the UALCAN database, along with western blot. CCK-8, EdU, and wound healing, together with transwell and western blot assays were adopted to assess the capabilities of cells to proliferate, migrate, invade, and epithelial-mesenchymal transition (EMT). Cell apoptosis was appraised utilizing TUNEL as well as western blot. Glycolysis was measured by western blot and kits. Enhancer of zeste homolog 2 (EZH2) expression in HCC cells was detected by western blot. Co-IP verified the combination of GGCT and EZH2. Moreover, PI3K/AKT pathway-related proteins were assessed employing western blot. Results GGCT expression was conspicuously upregulated in HCC samples and HCC cells. GGCT silencing repressed HuH-7 cell proliferative, invasive, and migratory capabilities as well as EMT, whereas facilitated cell apoptosis. In addition, GGCT silencing inhibited PTEN/PI3K/AKT pathway-mediated glycolysis. EZH2 was highly expressed in HCC cells and the interaction of GGCT and EZH2 was verified. Overexpression of EZH2 reversed the effects of GGCT silencing on HuH-7 cell proliferation, migration, invasion, cell apoptosis, and glycolysis. Moreover, the PTEN inhibitor SF1670 reversed the effects of GGCT silencing and EZH2 overexpression on the glycolysis and malignant process in HuH-7 cells. Conclusion In conclusion, GGCT silencing restrained the proliferation and metastasis, and promoted apoptotic levels of HCC cells via regulating PTEN/PI3K/AKT pathway-mediated glycolysis, which might offer a prospective candidate in treating HCC.